Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Siswa Pada Elemen Rencana Biaya Dan Penjadwalan Konstruksi Bangunan Di Smk Negeri 1 Pariaman - Yunika Meicelia Putri; Henny Yustisia (Jurnal Vokasi Mekanika (VoMek), 2025)
This lowed studied outcomes from students element a cost planning and scheduling of building construction element in choosing the PBL learning model. The researched waste make to determiner how effective the PBL studies model is in improve college studies outcoms through the elements of Cost Planning and Scheduling of Building Construction. The type of researched former attempt researched by affected tentative design form. The number of researched samples used was 45 people: 20 XI DPIB 1 students the attempt class, then 25 XI DPIB 2 the control clases. This attempt classes used Problem Based Learning (PBL) model. The researched wased carri off by giving test instrumental form of pretests with posttests. For the test of test questions, has been conducted in clases XI DPIB 2college SMKN 1 Padang within 26 respondents. This studies show that PBL can improve college studies outcomes in the matter of calculating foundation work. This averrage value student sudeis outcom attempt class was 77.95 with control classes waste 61.76. In addition, this effect hypothes testing carried out usee this Indepedent Sample t-Test tes obtain t_count> t_table or 6.038> 2.01669 then Ha is accepted. Therefore, this studied proves that PjBL model could fix the studies achievement of DPIB XI class college on the elements of the Cost Plan and Building Construction Scheduling.